Identification of the metalloregulatory element of the plasmid-encoded arsenical resistance operon. - San Francisco, M J (1990)
The regulatory region of the plasmid-encoded arsenical resistance (ars) operon was cloned as a 727-bp EcoRI-HindIII fragment. When cloned into a promoter probe vector this fragment conferred arsenite inducible tetracycline resistance in Escherichia coli, indicating that the fragment carried a regulatory gene, the arsR gene. A single region corresponding to -35 and -10 promoter recognition sites was identified. The transcriptional start site of the mRNA was determined by primer extension. The sequence has an open reading frame for a potential 13,179 Da polypeptide, termed the ArsR protein. The fragment was cloned into a temperature regulated expression vector. A protein with an apparent molecular mass of about 12 kDa was induced by either temperature or arsenite. This protein was purified and used to produce antibodies specific for the ArsR protein.